Different forms of decision-making involve changes in the synaptic strength of the thalamic, hippocampal, and amygdalar afferents to the medial prefrontal cortex - López-Ramos, Juan Carlos; Guerra-Narbona, Rafael; Delgado-García, José M. (Frontiers in Behavioral Neuroscience, 2015)
Decision-making and other cognitive processes are assumed to take place in the prefrontal cortex. In particular, the medial prefrontal cortex is identified in rodents by its dense connectivity with the mediodorsal thalamus, and because of its inputs from other sites, such as hippocampus and amygdala. The aim of this study was to find a putative relationship between the behavior of mice during the performance of decision-making tasks that involve penalties as a consequence of induced actions, and the strength of field postsynaptic potentials evoked in the prefrontal cortex from its thalamic, hippocampal, and amygdalar afferents. Mice were chronically implanted with stimulating electrodes in the mediodorsal thalamus, the hippocampal CA1 area, or the basolateral amygdala, and with recording electrodes in the prelimbic/infralimbic area of the prefrontal cortex. Additional stimulating electrodes aimed at evoking negative reinforcements were implanted on the trigeminal nerve. Field postsynaptic potentials evoked at the medial prefrontal cortex from the three selected projecting areas during the food/shock decision-making task decreased in amplitude with shock intensity and animals’ avoidance of the reward. Field postsynaptic potentials collected during the operant task also decreased in amplitude (but that evoked by amygdalar stimulation) when lever presses were associated with a trigeminal shock. Results showed a general decrease in the strength of these potentials when animals inhibited their natural or learned appetitive behaviors, suggesting an inhibition of the prefrontal cortex in these conflicting situations.